2021
DOI: 10.1177/0308518x211026321
|View full text |Cite
|
Sign up to set email alerts
|

‘Locked in the Rat Race’: Variegated financial subjectivities in the United Kingdom

Abstract: In the past four decades, the UK welfare state has been continuously reduced while asset ownership has gained in importance. Rather than relying on publicly funded welfare when not working, individuals are expected to mitigate future risks such as ill health, unemployment or old-age poverty through accumulating assets. Previous research employing a Foucauldian governmentality framework has explored how these norms of asset accumulation come into being through institutional changes and discourses. Documenting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…First, the findings presented suggest that gender is a key dynamic of variegated financial subjectivities (Lai 2017, Pellandini-Simanyi and Banai 2021, Agunsoye 2021. While male respondents tended to employ some of the rationale of the everyday investor, who perceives risk as positive and generative of income and employs individualistic ways to achieve maximum returns, female respondents were more likely to distance themselves from the financialised subjectivity of the everyday investor.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…First, the findings presented suggest that gender is a key dynamic of variegated financial subjectivities (Lai 2017, Pellandini-Simanyi and Banai 2021, Agunsoye 2021. While male respondents tended to employ some of the rationale of the everyday investor, who perceives risk as positive and generative of income and employs individualistic ways to achieve maximum returns, female respondents were more likely to distance themselves from the financialised subjectivity of the everyday investor.…”
Section: Discussionmentioning
confidence: 87%
“…Through these financial products, 'investor-subjects' (Langley 2006, p. 925) are expected to accumulate assets to provide for their later life, adopting financial strategies to manage the relationship between risk and reward for their assets, such as portfolio diversification. Yet, research has shown that individuals do not blindly follow these rationales: instead, financial rationales become enmeshed with everyday rationalities, resulting in variegated financial subject positions (Lai 2016, Pellandini-Simanyi and Banai 2021, Agunsoye 2021. Even those whose behaviour most closely resembles the theorised investor subject display a reluctance to adopt the underlying rationale associated with it, maintaining a critical lens towards financial institutions (Agunsoye 2021).…”
Section: Asset Accumulation In the Ukmentioning
confidence: 99%
See 2 more Smart Citations
“…To address this gap, we turn to research on everyday financialization, which challenges the monolithic theorization of the financial subject (Agunsoye, 2021;Lai, 2017;Pellandini-Simanyi & Banai, 2020). Through predominantly qualitative research, studies in this field have revealed the ways in which logics of finance become intertwined with everyday rationalities.…”
Section: Introductionmentioning
confidence: 99%